ANALISIS PERHITUNGAN HARGA POKOK PRODUKSI (HPP) DENGAN METODE FULL COSTING DALAM PENENTUAN HARGA JUAL PRODUK TENUN IKAT (Studi Kasus Pada Sanggar M’bola So Desa Hewuli Kabupaten Sikka) - Veronika Relu Suban; Maria E. D. Tunti; Suhartati Suhartati (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze the production cost calculation process previously applied by the M'bola So weaving workshop, to calculate the cost of goods manufactured (COGM) of ikat weaving products using the full costing method, and to analyze the suitability of the selling prices set by the workshop with the resulting COGM. This is a case study using a quantitative approach with data collected through interviews, observation, and documentation, then analyzed using the full costing method, which accounts for all elements of production cost, both fixed and variable. The results show that: (1) the production cost calculation previously carried out by the workshop was still simple and did not classify costs systematically into raw material, direct labor, and overhead components, and had never included equipment depreciation; (2) the COGM calculated using the full costing method for one production cycle yielded Rp845,000 for large-motif cloth, Rp700,000 for small-motif cloth, and Rp340,000 for shawls, all higher than the workshop's own estimates of Rp750,000, Rp450,000, and Rp280,000 respectively; and (3) the selling prices currently set by the workshop are not yet fully consistent with the full-costing COGM, with the small-motif cloth and shawl sold below their real cost, resulting in unrecognized losses of Rp200,000 and Rp40,000 per unit, while only the large-motif cloth still generated a positive margin. A cost-plus pricing recommendation with a 30% mark-up is proposed to align selling prices with actual production costs.